Midwifery Care for Postpartum Women with Breast Milk Preparation and Lactation Management at PMB "Y" Kampung Bali, Bengkulu City in 2023 - Rismayani; Siskaputri, Poppy (Jurnal Kebidanan Besurek, 2023)
Breastfeeding is a natural and important process in providing nutrition and protection for babies. Success in breastfeeding still requires knowledge about breast milk and its management starting from pregnancy to the ongoing breastfeeding process or Continuity of Care (COC). Preparing to breastfeed involves several important steps including physical and mental preparation. This research aims to determine the implementation of comprehensive midwifery care in PMB "Y" Kampung Bali, Bengkulu City so that it can prepare and accompany pregnant women and their families in the breastfeeding process. The research was conducted using case study and observation methods. The research results show that the midwifery care provided to mothers and families is largely in accordance with midwifery care standards. The method for selecting comprehensive care needs to be improved so that supervisors can direct the care given to patients according to evidence-based care.